Simon Baruch : rebel in the ranks of medicine, 1840-1921 - Ward, Patricia Spain (History of American science and technology series., 1994)
This biography recounts the remarkable life of a Prussian/Polish Jew who immigrated to the United States as a teenager in the 1850s and became one of the nation's best-known physicians by the turn of the century. Ward reconstructs the life of a medical student in the South at the opening of the Civil War, the adventures of a Confederate surgeon, and the difficulties of a practitioner in Reconstruction South Carolina. Simon Baruch's physician's registers and his correspondence with colleagues afford the reader an immediate sense of the therapeutic dilemmas facing physicians and patients of his.